Rosario+Vampire. 02, Witches - Ikeda, Akihisa, 1976- (Shonen Jump advanced, 2008)
All-around average student Tsukune transfers to Monster High, where he discovers the turf war isn't between the jocks and the nerds but the vampires and the werewolves. In this episode, Tsukune learns that having a witch for a classmate can create a vexing hexing situations.